Management and cost accounting - Drury, Colin (Thomson Learning, 2004)
This is the Student's Manual to accompany the leading international textbook Management and Cost Accounting by Colin Drury. Updated to correspond with the 6th edition of the textbook, it providers brief descriptions of the designated questions in the main text and then gives detailed solutions to them. Together, the main text and the StudentÂ's manual form an ideal learning package. The problems allow students to pursue topics in more depth and to concentrate on the application of principles in management and cost accounting. The key topics are covered in detail and provide a superb opportunity to practise answering exam questions, many of which are taken from past papers of professional accountancy bodies such as CIMA, ACCA, AAT, ICAEW and ICAI